TLC‐bioautography identification and GC‐MS analysis of antimicrobial and antioxidant active compounds in Musa × paradisiaca L. fruit pulp essential oil. Issue 3 (4th January 2019) - Fahim, Mohd.; Ibrahim, Mohammad; Zahiruddin, Sultan; Parveen, Rabea; Khan, Washim; Ahmad, Sayeed; Shrivastava, Birendra; Shrivastava, A.K.
Abstract: Introduction: The absence of microbial growth and resistance to oxidative deterioration in fruits of Musa × paradisiaca L. (bananas) is an indication of the presence of antimicrobial and antioxidant metabolites. Objective: In order to investigate the secondary metabolomic spectrum as well as the active antimicrobial and antioxidants present in essential oils (EOs) from fruits of different geographical areas of M. × paradisiaca, gas chromatography‐mass spectroscopy (GC‐MS) principal component data correlation analysis is complemented with antimicrobial assays and phytochemical and bioautographic antioxidant fingerprints with thin layer chromatography (TLC). Methodology: An EO was obtained by steam distillation and subjected to GC‐MS and TLC for metabolomic profiling from fruit pulp. The antimicrobial potential was tested in both Escherichia coli as a gram negative and Bacillus subtilis as a gram positive microbe. Potential antioxidant metabolites were identified through TLC‐bioautography and GC‐MS analysis of active zones. Results: A maximum of 0.56% v / w EO was isolated from fruit pulps of M. × paradisiaca . Minimum inhibitory concentrations (MICs) against B. subtillis and E. coli were 0.25 and 0.35 μg/mL, respectively. Thus, 56 metabolites were identified through GC‐MS. The major abundant antimicrobial metabolites found in EOs are α‐thujene, γ‐terpinene, α‐ and β‐pinene, sabinene, β‐myrcene, limonene, α‐capaene, caryophyllene and ( Z, E )‐α farnesene. Aceteugenol, palmitic acid, stearic acid, palmitin, and stearin were identified as antioxidant metabolites. Principal component analysis of metabolite data reveals correlations and a clear separation based on metabolites obtained from various areas. Conclusion: The data generated using metabolic profiling and cluster analysis helped to identify antimicrobial and antioxidant compounds in M. × paradisiaca . Abstract : The essential oil (EO) of Musa x paradisiaca L. was tested for antimicrobial potential against Escherichia coli and Bacillus subtilis which showed minimum inhibitory concentrations as 0.25 and 0.35 μg/mL, respectively. Further, GCMS analysis of EO resulted in identification of 56 metabolites whereas TLC bioautography depicted presence of antioxidant metabolites. Principal component analysis of metabolite data reveals correlations and a clear separation based on metabolites obtained from five different areas of accession.